Insights into key factors affecting bioconversion efficiency of rattan biomass: The supramolecular structural variations of cellulose. (February 2023) - Ling, Zhe; Wang, Jiajun; Zhao, Jinyi; Feng, Long; Ma, Jianfeng; Liu, Xinge
Graphical abstract: Highlight: Rattan cane was firstly used for representative biomass for enzymatic conversion. Continuous mild alkaline treatments were applied for structural variation. The conversion yield of treated rattan cellulose reached theoretically 100 %. Cellulose supramolecular structures were important factors affecting bioconversion. Abstract: Global energy concerns urged us to search for sufficient utilization of biomass to renewable energy. Herein, rattan biomass displaying herbaceous species-like anatomy and hardwood-like chemical composition was used as model of lignocellulose to determine its recalcitrance inhibiting efficient bioconversion. Delignification and continuous mild alkaline treatments were applied for deconstruction of rattan cane ( Calamus simplicifolius ) followed by cellulase enzymatic hydrolysis. Cellulose supramolecular structural variations were proved to be the major reason for the enhanced hydrolysis in addition to the removal of lignin and hemicelluloses matrix. Lowered crystallinity (50–65 %) as well as swelled crystallite sizes (4.8–5.0 nm) during allomorphic transformation favored the enhanced hydrolysis, rather than the crystalline cellulose II. Moreover, well-distributed separation and fibrillation of cellulose elementary fibrils also contributed to glucose yield promotion. The study will provide new insights to the strategy to efficient bioconversion of lignocellulosic biomass.